Vacuum High-Temperature Brazing of 3003 Aluminum Alloy - Makymova S. V.; Voronov V. V.; Kovalchuk P. V.; Shapiro A. Е. (Журнал інженерних наук)
Brazing filler metals based on the Al-Si system are widely used for brazing aluminum alloys. Their melting point is 577 °С (eutectic). It is necessary to conduct comprehensive studies of the technological properties of experimental filler metals and brazed joints to create a brazing filler metal with a reduced melting temperature for vacuum brazing of thin-walled aluminum products made of alloy 3003. The paper presents the research results on high-temperature vacuum brazing of aluminum alloy 3003 with Al-Cu-(Si, Mg) filler metal. It was determined that the amount of magnesium in the filler should be limited due to the risk of porosity formation associated with magnesium vaporization. It was identified that reducing the magnesium content increases the liquidus temperature above 530–550 °C. Therefore, experimental alloys require additional alloying with depressant elements, particularly silicon, to achieve the required melting temperature level. The chemical inhomogeneity of the filler in the initial state (after rapid solidification from the liquid state) and the structure of the brazed joints were investigated using micro-X-ray spectral analysis. Through empirical means, it was determined that a magnesium content of 1.5 % by weight in the filler allows for producing high-quality brazed joints without visible defects. In this case, shear strength is in the range of 0.6–0.7 of the strength of the base material. Tests of brazed joints for three-point bending resulted in an angle close to 180°, which indicates the promising use of experimental brazing filler metal in vacuum brazing of aluminum alloy 3003.